ANALISI NILAI TAMBAH KACANG SANGRAI UD. MERPATI DI DESA TOMBASIAN ATAS KECAMATAN KAWANGKOAN BARAT - Filia Christi Batas; Leonardus Ricky Rengkung; Juliana Ruth Mandei (AGRI-SOSIOEKONOMI, 2020)
The purpose of this research is to analyze the value added of raw peanuts to roasted peanuts. This research was conducted at UD. â€œMerpatiâ€ at Tombasian Atas Village, West Kawangkoan Sub-district. Primary data collection is done through direct interviews, with the help of a list of questions, to the owner who is a entrepreneur and manager of the roasted peanuts processing industry and to employees. Added value is the difference in the value of output with the value of the main raw materials and the contribution of other inputs (IDR/ kg). The results showed that the added value obtained of 1 kg of raw peanuts at a price of IDR 4,000 processed into roasted peanuts at a price of IDR. 22,000, - Add value for 1 kg of roasted peanuts that have been packaged, that is IDR. 45,000,-.*eprm*